2020
DOI: 10.2196/24375
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Fever of Unknown Origin Intelligent Diagnosis Based on Clinical Data: Model Development and Validation

Abstract: Background Fever of unknown origin (FUO) is a group of diseases with heterogeneous complex causes that are misdiagnosed or have delayed diagnoses. Previous studies have focused mainly on the statistical analysis and research of the cases. The treatments are very different for the different categories of FUO. Therefore, how to intelligently diagnose FUO into one category is worth studying. Objective We aimed to fuse all of the medical data together to au… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Our systematic search could only identify studies explicitly mentioning transfer learning or a similar term (e.g. ‘knowledge transfer’), however this does not seem to be a common practice in medical text analysis [ 121 123 ]. Future studies are warranted about the impact of specific models (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Our systematic search could only identify studies explicitly mentioning transfer learning or a similar term (e.g. ‘knowledge transfer’), however this does not seem to be a common practice in medical text analysis [ 121 123 ]. Future studies are warranted about the impact of specific models (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…59,60 Unlike the above-mentioned diagnostic and predictive tools, AUC values that quantified discriminative power were not used as the main evaluation indictor for classification tools, with only four studies reported the values of AUC. 54,59,60,62 Instead, model accuracy 54,56,58,59,62 and precision 55,56,61 were the favorable indicator evaluating model performance. Other supporting indices included recall rates, 58,61 F-1 score, 56,58,59 and Kappa value.…”
Section: Validation Methods and Outcomes Measuresmentioning
confidence: 99%
“…Chinese medicine syndromes of liver cancer, 58 various causes for fever of unknown origin, 55 multidisease and multilesion diagnosis, 56 and the severity of diabetic retinopathy. 60…”
Section: Clinical Benefits and Therapeutic Areasmentioning
confidence: 99%
“…Therefore, the first stage of etiology screening is very important. If the etiology of a FUO can be classified into one category, no matter the disease that caused the FUO, the direction of diagnosis can be determined, which is of great significance to physicians (16,17). Previous studies of classic FUO have focused on the etiology, prognosis, or diagnosis of classic FUO (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of classic FUO have focused on the etiology, prognosis, or diagnosis of classic FUO (18,19). So far, few researchers have studied the etiological causes of classic FUO from the perspective of clinical prediction models and machine learning (ML) (16). In recent years, ML has been widely used in the medical field and has achieved good results in disease diagnosis, risk assessment, and other factors (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%